INOVASI KEBIJAKAN PENGURANGAN SAMPAH PLASTIK DI KOTA BALIKPAPAN - Thalita Rifda Khaerani; Rosa Anggraeny; Muhammad Gilang Akbar Ramadhan (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
The problem of plastic waste confronts the Balikpapan City government in implementing regulations and innovations that are continuously updated in reducing plastic waste management in Balikpapan City. This is done because the community and business actors are still dominant who ignore environmental conditions and applicable regulations. This study aims to analyze the innovation efforts to reduce plastic waste, as well as to describe the inhibiting factors for plastic waste reduction innovation at the Balikapapan City Environmental Service. The type of research is descriptive qualitative research with data collection techniques, library techniques and field techniques with observation, interviews, documentation and focus group discussions (FGD) along with data analysis techniques in the form of data condensation, data presentation and drawing conclusions and verification. The results showed that the policy innovation for reducing single-use plastic waste was carried out through several stages, namely generating opportunities through several Regional Regulations and Mayor Regulations there was a positive trend of changes in community behavior. Developing and Designing with the participation and involvement of the community in the realization of the implementation of innovation in reducing plastic products/packaging. Replicating and appointing through socialization and the issuance of local regulations have an impact on the growth of public awareness. Analyzing and learning there are positive changes but they are running slowly due to the Covid-19 pandemic in the implementation process which is not optimal. And found three factors inhibiting the innovation process, namely, pressure and burden, dealing with failure, and organizational arrangements